Silorane- and high filled-based"low-shrinkage" resin composites: shrinkage, flexural strength and modulus - Cesar Augusto Galvão Arrais; Marcelo Tavares de Oliveira; Donald Mettenburg; Frederick Allen Rueggeberg; Marcelo Giannini (Sociedade Brasileira de Pesquisa Odontológica, 2013)
This study compared the volumetric shrinkage (VS), flexural strength (FS) and flexural modulus (FM) properties of the low-shrinkage resin composite Aelite LS (Bisco) to those of Filtek LS (3M ESPE) and two regular dimethacrylate-based resin composites, the microfilled Heliomolar (Ivoclar Vivadent) and the microhybrid Aelite Universal (Bisco). The composites (n = 5) were placed on the Teflon pedestal of a video-imaging device, and VS was recorded every minute for 5 min after 40 s of light exposure. For the FS and FM tests, resin discs (0.6 mm in thickness and 6.0 mm in diameter) were obtained (n = 12) and submitted to a piston-ring biaxial test in a universal testing machine. VS, FS, and FM data were submitted to two-way repeated measures and one-way ANOVA, respectively, followed by Tukey's post-hoc test (a = 5%). Filtek LS showed lower VS than did Aelite LS, which in turn showed lower shrinkage than did the other composites. Aelite Universal and Filtek LS exhibited higher FS than did Heliomolar and Aelite LS, both of which exhibited the highest FM. No significant difference in FM was noted between Filtek LS and Aelite Universal, while Heliomolar exhibited the lowest values. Aelite LS was not as effective as Filtek LS regarding shrinkage, although both low-shrinkage composites showed lower VS than did the other composites. Only Filtek LS exhibited FS and FM comparable to those of the regular microhybrid dimethacrylate-based resin composite.